2005
DOI: 10.1246/cl.2005.1614
|View full text |Cite
|
Sign up to set email alerts
|

Location of Vanadium(IV) in VAPO-5 as Studied by Hyperfine Sublevel Correlation Spectroscopy

Abstract: Vanadium(IV) framework substitution in aluminophosphate molecular sieves has been explored by electron spin resonance (ESR) and hyperfine sublevel correlation (HYSCORE) spectroscopy. In both as-synthesized and hydrated materials V(IV) exists as VO2+ species that coordinates to two framework oxygen atoms and presumably three water molecules in a distorted octahedral geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Careful inspection of the X-band spectrum reveals that two species with slightly different spin-Hamiltonian parameters contribute to the overall spectral pattern. The spin Hamiltonian parameters of the two species deduced from computer simulation of the X- and Q-band spectra are reported in Table and agree with previous literature data. ,,, In Table the signs of the experimental hfi tensor elements were chosen such that agreement with the signs of the calculated A values was maintained (vide infra), i.e., assuming the sign of the experimental A values to be all negative, in agreement with previous experimental and theoretical work. , The abundance ratio between the two species was found, based on computer simulation, to be of the order of 1:0.7 in fair agreement with the results of ref .…”
Section: Results and Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Careful inspection of the X-band spectrum reveals that two species with slightly different spin-Hamiltonian parameters contribute to the overall spectral pattern. The spin Hamiltonian parameters of the two species deduced from computer simulation of the X- and Q-band spectra are reported in Table and agree with previous literature data. ,,, In Table the signs of the experimental hfi tensor elements were chosen such that agreement with the signs of the calculated A values was maintained (vide infra), i.e., assuming the sign of the experimental A values to be all negative, in agreement with previous experimental and theoretical work. , The abundance ratio between the two species was found, based on computer simulation, to be of the order of 1:0.7 in fair agreement with the results of ref .…”
Section: Results and Discussionsupporting
confidence: 81%
“…The spin Hamiltonian parameters of the two species deduced from computer simulation of the X-and Q-band spectra are reported in Table 1 and agree with previous literature data. 19,20,45,62 In Table 1 the signs of the experimental hfi tensor elements were chosen such that agreement with the signs of the calculated A values was maintained (vide infra), i.e., assuming the sign of the experimental A values to be all negative, in agreement with previous experimental and theoretical work. 40,59 The abundance ratio between the two species was found, based on computer simulation, to be of the order of 1:0.7 in fair agreement with the results of ref 45.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The spectral similarity of (Co, V)APO-5-0.05-0.03 to VAPO-5 indicates that V sites in the (Co, V)APO-5 and VAPO-5 molecular sieves had a similar local geometry [27], viz. part of them was present in the state of isolated square-pyramidal and/or distorted octahedral vanadyl-like (VO 2+ ) species [3,12,15,22,33,37]. After calcination, no ESR signal was detected, showing that all V 4+ ions were oxidized to the EPR-inactive V 5+ .…”
Section: Catalyst Synthesis and Characterizationmentioning
confidence: 99%
“…Some authors suggested that V 4+ substitutes for Al 3+ [38], while other research groups believe it replaces P 5+ [22,33,34]. Nagarajan et al very recently deduced from ESR and hyperfine sublevel correlation (HYSCORE) spectroscopy that VO 2+ species is present in the as-synthesized VAPO-5 by equatorially coordinating to two framework oxygen atoms and presumably three water molecules in a distorted octahedral geometry with phosphorus and aluminum framework atoms in the second coordination shell [37]. Despite of the controversy, the common point in all the well-documented literature reports is that vanadyl-like species is anchored to the framework via coordination to two framework oxygen atoms.…”
Section: Catalyst Synthesis and Characterizationmentioning
confidence: 99%